Proceedings of the International Congress on Information and Communication Technology ICICT 2015, Volume 1 - Satapathy, Suresh Chandra; Bhatt, Yogesh Chandra; Joshi, Amit.; Mishra, Durgesh Kumar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This volume contains 69 papers presented at ICICT 2015: International Congress on Information and Communication Technology. The conference was held during 9th and 10th October, 2015, Udaipur, India and organized by CSI Udaipur Chapter, Division IV, SIG-WNS, SIG-e-Agriculture in association with ACM Udaipur Professional Chapter, The Institution of Engineers (India), Udaipur Local Centre and Mining Engineers Association of India, Rajasthan Udaipur Chapter. This volume contains papers mainly focused on ICT for Managerial Applications, E-governance, IOT and e-Mining.
Chapter 1. Resource Management Using Virtual Machine Migrations -- Chapter 2. Framework of Compressive Sampling with its Applications to One and Two Dimensional Signals -- Chapter 3. Carbon Footprints Estimation of a Novel Environment-aware Cloud Architecture -- Chapter 4. Examining Usability of Classes in Collaboration with SPL Feature Model -- Chapter 5. Do Bad Smells follow some Pattern? -- Chapter 6. Ultra-Wideband Antenna with Triple Band Notched Characteristics -- Chapter 7. Utilizing NL Text for generating UML Diagrams -- Chapter 8. 2-D Photonic Crystal Based Solar Cell -- Chapter 9. Parallel Implantation of Frequent Itemset Mining Using Inverted Matrix Based on OpenCL -- Chapter 10. Extended Visual Secret Sharing with Cover Images Using Half Toning -- Chapter 11. Resonant Cavity Based Optical Wavelength De-multiplexer Using SOI Photonic Crystals -- Chapter 12. A Frequency Reconfigurable Antenna with Six Switchable Modes for Wireless Application -- Chapter 13. Comparative Analysis of Digital Watermarking Techniques -- Chapter 14. Design and Analysis of 1x6 Power Splitter Based on the Ring Resonator -- Chapter 15. Performance Evaluation of Vehicular Ad-hoc Network Using SUMO and NS2 -- Chapter 16. An Intrusion Detection System for detecting Denial of Service Attack in Cloud by Using Artificial Bee Colony -- Chapter 17. Multi-Cavity Photonic Crystal Waveguide Based Ultra-Compact Pressure Sensor -- Chapter 18. Role Based Access Mechanism/Policy for Enterprise Data in Cloud -- Chapter 19. Big Data in Precision Agriculture through ICT: Rainfall Prediction Using Neural Network Approach -- Chapter 20. Evaluating Interactivity with respect to Distance and Orientation Variables of GDE Model -- Chapter 21. Comparative Evaluation of SVD-TR Model for Eye-Gaze Based Systems -- Chapter 22. Identity Based Key Management -- Chapter 23. Firefly Algorithm Hybridized with Flower Pollination Algorithm for Multimodal Functions -- Chapter 24. Uniqueness in User Behavior while Using the Web -- Chapter 25. Prediction of ERP Outcome Measurement and User Satisfaction by using Adaptive Neuro Fuzzy Inference System and SVM Classifiers Approach -- Chapter 26. UWB Antenna with Band Rejection for WLAN/WIMAX Band -- Chapter 27. Consequence of PAPR Reduction in OFDM System on Spectrum & Energy Efficiencies Using Modified PTS Algorithm -- Chapter 28. Energy Efficient Resource Provisioning Through Power Stability Algorithm in Cloud Computing -- Chapter 29. Comparative Analysis of Scalability and Energy Efficiency of Ordered Walk Learning Routing Protocol -- Chapter 30. A Novel Technique for Voltage Flicker Mitigation Using Dynamic Voltage Restorer -- Chapter 31. Gaussian Membership Function Based Speaker Identification Using Score Level Fusion of MFCC and GFCC -- Chapter 32. Efficient Local and Global Color Histogram Feature for Color Content Based Image Retrieval System -- Chapter 33. Energy Efficient Pollution Monitoring System Using Deterministic Wireless Sensor Networks -- Chapter 34. Development of Electronic Control System to Automatically Adjust Spray Output -- Chapter 35. Social Impact Theory Based Node Placement Strategy for Wireless Sensor Networks -- Chapter 36. Bang of Social Engineering in Social Networking Sites -- Chapter 37. Internet of Things (IoT): In a Way of Smart World -- Chapter 38. A Study of Routing Protocols for MANETs -- Chapter 39. Modelling Social Aspects of E-agriculture in India for Semantic Web -- Chapter 40. An Efficient Adaptive Data Hiding Scheme for Image Steganography -- Chapter 41. A Five-Layer Framework for Organizational Knowledge Management -- Chapter 42. A Survey on Big Data Architectures and Standard Bodies -- Chapter 43. Generating Data for Testing Community Detection Algorithms -- Chapter 44. Metamorphic Malware Detection using LLVM IR and Hidden Markov Model -- Chapter 45. Object Based Graphical User Authentication Scheme -- Chapter 46. Efficient Density Based Clustering Using Automatic Parameter Detection -- Chapter 47. Implementation of GIS Based Decision Support System for Crop Selection: A Case for Autumn (Kharif) Crops -- Chapter 48. WT Based Distributed Generation Location Minimizing Transmission Loss Using Mixed Integer Non-Linear Programming in Deregulated Electricity Market -- Chapter 49. Use Case Based Software Change Analysis and Reducing Regression Test Effort -- Chapter 50. Tackling Supply Chain Management through RFID: Opportunities and Challenges -- Chapter 51. Quality Improvement of Fingerprint Recognition System -- Chapter 52. A Composite Approach to Digital Video Watermarking -- Chapter 53. Effective Congestion less Dynamic Source Routing for Data Transmission in MANETs -- Chapter 54. Implementation & Integration of Cellular/GPS Based Vehicle Tracking System with Google Maps Using a Web Portal -- Chapter 55. Image Segmentation Using Two Dimensional Renyi Entropy -- Chapter 56. Supervised Learning Paradigm Based on Least Square Support Vector Machine for Contingency Ranking in a Large Power System.-Chapter 57. Process flow for Information Visualization in Biological Data -- Chapter 58. A Performance Analysis of High Level MapReduce Query Languages in Big Data -- Chapter 59. Variance Based Clustering for Balanced Clusters in Growing Datasets -- Chapter 60. Conceptual Framework for Knowledge Management in Agriculture Domain -- Chapter 61. Modularity-Based Community Detection in Fuzzy Granular Social Networks -- Chapter 62. Auto Characterization of Learning Materials: An Adaptive Approach to Personalized Learning Material Recommendation -- Chapter 63. Hadoop with Intuitionistic Fuzzy C-Means for Clustering in Big Data -- Chapter 64. A Framework for Group Decision Support System using Cloud Database for Broadcasting Earthquake Occurrences -- Chapter 65. Advanced Persistent Threat Model for Testing Industrial Control System Security Mechanisms -- Chapter 66. E-Reader Deployment in Namibia: Fantasy or Reality? -- Chapter 67. Multi-Region Pre-Routing in Large Scale Mobile Ad-hoc Networks (MRPR).-Chapter 68. Challenges Faced in Deployment of e-Learning Models in India -- Chapter 69. A Novel Cross-Layer Mechanism for Improving H.264/AVC Video Transmissions over IEEE 802.11n WLANs.
Keywords: Telecommunication; Data mining; Data protection; Communications Engineering, Networks; Data Mining and Knowledge Discovery; Data and Information Security